Global distribution and evolutionary transitions of floral symmetry in angiosperms - Wang, Yunyun; Luo, Ao; Lyu, Tong; Dimitrov, Dimitar; Liu, Yunpeng; Li, Yichao; Xu, Xiaoting; Freckleton, Robert P.; Hao, Zhanqing; Wang, Zhiheng (Science Advances, 2023)
Floral symmetry plays an important role in plant-pollinator interactions and may have remarkable impacts on angiosperm diversification. However, spatiotemporal patterns in floral symmetry and drivers of these patterns remain unknown. Here, using newly compiled floral symmetry (actinomorphy versus zygomorphy) data of 279,877 angiosperm species and their distributions and phylogenies, we estimated global geographic patterns and macroevolutionary dynamics of floral symmetry. We found that frequency of actinomorphic species increased with latitude, while that of zygomorphic species decreased. Solar radiation, present-day temperature, and Quaternary temperature change correlated with geographic variation in floral symmetry frequency. Evolutionary transitions from actinomorphy to zygomorphy dominated floral symmetry evolution, although the transition rate decreased with decreasing paleotemperature throughout the Cenozoic. Notably, we found that zygomorphy may not favor diversification of angiosperms as previously observed in some clades. Our study demonstrates the influence of (paleo)climate on spatiotemporal patterns in floral symmetry and challenges previous views about role of flower symmetry in angiosperm diversification. (Paleo)climate profoundly influenced spatiotemporal patterns of angiosperm floral symmetry.